Peran Job Order Costing dalam Akurasi Penentuan Harga Jual Produk Pada Usaha D’Wish Cafe - Taufiq Saputra; Fifi Nabilla Opratiwi; Riska Putri Kirana; Hasan Al Farobi (PT. Hasba Edukasi Mandiri, 2025)
D'wish Cafe, as a provider of coffee and light snacks in Bekasi, faces challenges in determining optimal selling prices and accurately evaluating the profitability of each of its products amidst fierce competition. This study examines the implementation and role of Job Order Costing (JOC) in improving the accuracy of determining product selling prices at D'wish Cafe. Through a qualitative approach with management interviews and observations, it was found that although D'wish Cafe has informally applied Job Order Costing (JOC) principles in identifying direct costs for custom orders (e.g., catering or special cake orders), the formalization of this system is still limited to regular products. A more systematic application of Job Order Costing (JOC) is believed to provide more precise cost data for each menu item, enable more strategic pricing, and provide in-depth insights to identify the most profitable products and areas of efficiency that need to be improved.